PENGARUH PERMAINAN SNAKES AND LADDERS MODIFIKASI TERHADAP PENGENALAN KOSAKATA BAHASA INGGRIS DI TAMAN KANAK-KANAK ANGKASA LANUD PADANG - Silvia Seprianti; Elise Muryanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The low ability of children to understand English vocabulary, which is a provision for children to adapt to the global world, is the background behind this research. This research was conducted with the aim of identifying the results of a modified snakes and ladders game to introduce knowledge of English at the Angkasa Lanud Padang Kindergarten. The illustrations in this research are 24 children at Angkasa Lanud Padang Children's Park, 12 children in the control category and 12 children in the experimental category. This type of research is quantitative and uses research procedures using quasi-experimental research concepts. Researchers used information gathering methods by means of word tests and action tests. In information analysis, carry out normality experiments and homogeneity experiments. Based on the results of the pre-test and post-test, there is generally a gain score in the research category of 10.25 and the average gain score in the supervision category is 4.08. From the results experienced there is an important demonstration between the supervision categories as well as research categories. That's the conclusion that Ha obtained and Ho rejected. The research results show the results of using a modified snakes and ladders game to introduce understanding of English to young children.